2019
DOI: 10.1016/j.aprim.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Prescripción enfermera: análisis de concepto

Abstract: ResumenObjetivoExaminar críticamente el concepto de prescripción enfermera mediante el estudio de los antecedentes y una revisión de la literatura científica con el fin de desarrollar una concepción precisa de esta actuación enfermera e identificar los elementos esenciales que envuelven este concepto.MétodoAplicación del procedimiento de análisis de concepto descrito por Wilson y adaptado por Avant.ResultadosEl concepto de prescripción enfermera implica prescribir por parte de la enfermera el mejor régimen ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Regarding NP in Spain, similar results for collaborative and autonomous or independent competencies were obtained in a Catalonian study. The NP is linked to the nursing process and contributes effectively to the management of healthcare [ 23 ]. Contrasting the information with other countries, in the United Kingdom nurses can prescribe and they have demonstrated that training is essential, as well as the preservation of the role of nurses in care, thus not focusing all their efforts on prescribing drugs but on prescribing care [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding NP in Spain, similar results for collaborative and autonomous or independent competencies were obtained in a Catalonian study. The NP is linked to the nursing process and contributes effectively to the management of healthcare [ 23 ]. Contrasting the information with other countries, in the United Kingdom nurses can prescribe and they have demonstrated that training is essential, as well as the preservation of the role of nurses in care, thus not focusing all their efforts on prescribing drugs but on prescribing care [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurse prescribing is the right of nursing practitioners to prescribe the most effective treatment for a patient’s health issue in nursing practice [ 1 ]. According to the report State of the World’s Nursing 2020 , an effective nurse-led care program can address the health needs of a growing population [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Outro aspecto importante sobre a prescrição de enfermagem é que assim como a (por exemplo, melhora da lesão a partir do curativo utilizado) (44,45) .…”
Section: Introductionunclassified